Financial indicators analysis on the computer software industry. - Choy, Shwu Fen (2014)
A strong IT industry will be the main driving force to push the economy of a country towards a higher level of performance. It will enhance productivity, create jobs within the industry as well as provide the impetus for industrialisation. In Singapore, the public has come to recognise that the potential contributions of the computer software industry are too important to be neglected.